If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2x^2+5x+23=-x2+3x+15
We move all terms to the left:
-2x^2+5x+23-(-x2+3x+15)=0
We add all the numbers together, and all the variables
-2x^2-(-1x^2+3x+15)+5x+23=0
We get rid of parentheses
-2x^2+1x^2-3x+5x-15+23=0
We add all the numbers together, and all the variables
-1x^2+2x+8=0
a = -1; b = 2; c = +8;
Δ = b2-4ac
Δ = 22-4·(-1)·8
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{36}=6$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(2)-6}{2*-1}=\frac{-8}{-2} =+4 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(2)+6}{2*-1}=\frac{4}{-2} =-2 $
| 89=w+14 | | q-40=38 | | x/(91/2)=(8)/(61/3) | | 2x+10=x+50,x | | 6x-4+2x=28+3x-12 | | 2(6y-20)=2y+1 | | 2(6y-20)=2y-1 | | 3x-2(-2x+3)=5 | | 16=q+3 | | 48+12k=-3(8-7k) | | 2(11x-8)=4x+5 | | 4x+56=90 | | 10=r+5 | | 4t+8=7t−7 | | 8n-10=7n | | (3y-4)+(5y+8)=20 | | 12y+25=3y-10 | | 17+t=23 | | 5x+1=–14 | | 2.5=m-2.5 | | 7+5r+3+5=1+7 | | 31=19+q | | -5(-9x-3)+5x=50x+15 | | 7+5r+3+5=1+1+7 | | 7+5r+3+4=1+1+7r | | 10=10+d | | 6n-63=4(4n+9)+11 | | 17+z=27 | | 6y÷3y=10 | | -3x*3x=0 | | X^2+5x-1622=0 | | x/8+34=180 |